The Influence of Supervision and Motivation on Teacher Performance at AR RAHMA Cidahu Vocational School, Sukabumi District - Rindiani Octhavia; Yepi Sopian (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted at AR RAHMA Cidahu Vocational School, Sukabumi Regency. This research was carried out in order to determine the effect of supervision and motivation on teacher performance at AR RAHMA Vocational School. The research method used is the Survey Method. The population in the study was 31 AR RAHMA Vocational School teachers, while the sampling technique used the Saturated Sampling method. Classical assumption tests, in addition to reliability and validity tests, are used to evaluate the instrument. Research data was tested using descriptive and associative frequency tests with coefficient of determination and multiple linear regression analysis. Supervision and motivation influence teacher performance, according to the research coefficient of determination of 45.5%. If the supervision (X1) and motivation (X2) variables have no value, then the Teacher Performance (Y) value is 0.316. The regression equation for supervision and motivation is 0.315 + (0.723) X1 + (0.483)X2, and the constant coefficient is 0.315. Coefficient β1 = 0.723, Coefficient β2 = 0.483